Biomarker changes after strenuous exercise can mimic pulmonary embolism and cardiac injury: a metaanalysis of 45 studies - Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Frankenstein, Lutz; Mereles, Derliz; Amr, Ali; Buß, Sebastian Johannes; Keller, Andreas; Giannitsis, Evangelos; Jensen, Katrin; Katus, Hugo; Meder, Benjamin (Clinical chemistry, 2015)
AbstractBACKGROUND. Biomarkers are well established for diagnosis of myocardial infarction [cardiac troponins, high-sensitivity cardiac troponins (hs-cTn)], ex
Gesehen am 15.06.2020